The Influence Of Digital Marketing And Product Quality On Online Purchase Intention Moderated By Product Variation - Setiawan, Zunan; Anwar, M.; Judijanto, Loso; Ilyas, Arifai; Elizabeth, Elizabeth (Universitas Dharma Wacana, 2024)
A Because the current online shopping phenomenon continues to grow, businesses must be aware of the importance of digital marketing and providing quality products so that customers can buy goods on the market. This study aims to examine and analyze the influence of digital marketing and product quality on purchase intention with the product variations as an moderating variable in Tokopedia aplication users. The method of research is using the quantitative and regression analysis. The sampling method used purposive sampling and the number of samples used in this study amounted to 60 respondent source was distribution of questionnaires to Tokopedia users in Indonesia by online via WhatsApp. The data analysed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of this study indicate that the digital marketing and product quality have a significant positive effect on purchase intention, while product variations not have a significant effect on purchase intention in Tokopedia aplication user. The product variations is able to moderate the influence of digital marketing and product quality on purchase intention. The findings of this study can be reference uses as reference for future researchers who will study similar problems. This research can also be used as evaluation material for management of companies that sell products on Tokopedia to pay more attention to digital marketing and product quality in order to make it easier to carry out marketing with a wider reach and increase consumer purchase intention